INNOVATION APPROACH IN VARIOUS COUNTRIES IN RESPONDING TO VOLATILITY-LITERATURE REVIEW STUDY - Nursyirwan, Vivi Iswanti; Purwana, Dedi; Suhud, Usep; Harahap, Irwan Leo Putra; Ardaninggar, Sasmita Sari; Diana, Diana (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
Innovation is one of the keys to the success of an organization. This literature review study aims to explore the supporting components of innovation and how the innovation approach is applied in various countries in the world. This study uses a literature review as a literature search material that has a large repository for academic studies, particularly in Elsevier (Scopus). The search for references was carried out by applying the inclusion criteria and exclusion criteria methods. Main search terms via search engines: (Innovative Work Behavior) and (Countries) and (Companies) and (Support) or (Impede), with searches from 2018 to 2020. This study uses a literary approach, with final results 12 The literature shows that there are at least 12 important components in an organization both internally and externally that are discussed in this research literature, including: management control systems, technology licenses, R&D, company size, sectoral characteristics and access to finance, company resources and dynamic external environmental capabilities, number of executives with financial background, company age, company size, forward-looking search, service ecosystem. Through this literature study, business agencies should pay attention to these variables in developing innovations that are an important part of organizational survival. Future studies need to add a longer time span with a wider database.